Extreme integral polynomials on a complex Banach space - Dineen, Seán (Mathematica Scandinavica, 2003)
We obtain upper and lower set-theoretic inclusion estimates for the set of extreme points of the unit balls of P_I(^n\!E) and P_N(^n\!E), the spaces of n-homogeneous integral and nuclear polynomials, respectively, on a complex Banach space E. For certain collections of Banach spaces we fully characterise these extreme points. Our results show a difference between the real and complex space cases.